NASIONALISASI PERUSAHAAN-PERUSAHAAN ASING MENUJU EKONOMI BERDIKARI - Wasino, Wasino (Paramita: Historical Studies Journal, 2016)
After Indonesia declared its independence, the management of the private companies became a big problem for a new government, Indonesia. Expropriation efforts for those western private plantation companies actually had been developed in the first year of the independence and it continued until the Dutch-Indonesian Round Table Conference. There were three processes passed through companiesâ transformation of the western private plantation in Indonesia, namely decolonization, Indonesia-nization and nationalization. Nationalization was legally based on the Indonesian Ordinance number 86 1958, but the real process occured since a year ago. Therefore,Â  Indonesia had to give financial compensation to the owner, but the reality was that this aspect was still unfinished until the end of Sukarno regime. The compensation had been continued in Suharto era and was fully paid in 2002.Â Setelah Indonesia menyatakan kemerdekaannya, manajemen perusahaan swasta menjadi masalah besar bagi pemerintahan baru, Indonesia. Upaya pengambilalihan bagi perusahaan perkebunan swasta Barat sebenarnya telah dikembangkan pada tahun pertama kemerdekaan dan itu berlanjut hingga Konferensi Meja Bundar Belanda-Indonesia. Ada tiga proses melewati transformasi perusahaan dari perkebunan swasta Barat di Indonesia, yaitu dekolonisasi, Indonesia-nization dan nasionalisasi. Nasionalisasi secara hukum berdasarkan jumlah Ordonansi Indonesia 86 tahun 1958, tetapi proses nyata terjadi sejak setahun yang lalu. Oleh karena itu, Indonesia harus memberikan kompensasi finansial kepada pemilik, tetapi kenyataannya adalah bahwa aspek ini masih belum selesai sampai akhir rezim Sukarno. Kompensasi telah berlanjut di era Soeharto dan telah dilunasi pada tahun 2002.Â Â